The prospects of a confederation: Ukraine, Poland, Lithuania, Belarus - KOSTIUK, OLEKSANDR (Journal of Education, Technology and Computer Science, 2016)
In the article the possibility of unification of Poland, Ukraine, Lithuania and Belarus in a confederal association. Analyzes the political, economic, military and social benefits of working in these countries. The reasons for creating this association of states is to protect the political and military aggression of Russia, and protection from the economic aggression of Western Europe.